School Management Digitalization Strategy To Improve Education Quality at State Vocational School 2 Gunungsitoli - Telaumbanua, Fajar Otolius; Telaumbanua, Eliagus; Waruwu, Suka’aro; Mendrofa, Syah Abadi (Economics and Business Journal (ECBIS), 2025)
This study aims to analyze the digitalization strategy of school management in improving the quality of education at SMK Negeri 2 Gunungsitoli. This research is motivated by the importance of digital transformation in the world of education, particularly in efficient, adaptive, and technology-based school management. The research method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. The research informants consisted of the principal, vice principal, teachers, and administrative staff. The results of the study indicate that the digitalization strategy has begun to be implemented through the use of technology in the learning process, the development of teachers' digital skills, and the integration of technology-based educational platforms. However, in its implementation, the school faces various obstacles, such as limited school internet (Wi-Fi) quota and low digital competence of some teachers. To overcome these obstacles, the school conducts internal training, utilizes offline learning media, and improves digital infrastructure. The conclusion of this study shows that the digitalization of school management contributes significantly to improving the quality of education, especially in terms of learning effectiveness, administrative efficiency, and strengthening teacher and student competence in the digital era